2015
DOI: 10.3892/ijo.2015.3197
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-reactive memory T cells from bone marrow: Spontaneous induction and therapeutic potential (Review)

Abstract: Cognate interactions between naïve tumor antigen (TA)-specific T cells and TA-presenting dendritic cells (DCs) are facilitated by secondary lymphoid organs such as lymph nodes or the spleen. These can result either in TA-specific tolerance or, depending on environmental costimulatory signals, in TA-specific immune responses. In the present review, we describe such events for the bone marrow (BM) when blood-borne TA, released from the primary tumor or expressed by blood circulating tumor cells or DCs enters the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 104 publications
(124 reference statements)
0
12
0
1
Order By: Relevance
“…In addition, HER2-enrich and basal-like carcinomas are characterized by highest CD8 tumor infiltrating lymphocytes and highest frequencies of memory T cells 25 , 26 . Researches in both human and mouse models have indicated that CD8 + T EM cells are enriched in the bone marrow of breast cancer patients/animals, but deficient in malignant effusions 27 - 29 . During the development of breast cancer, the human immune system is activated, and both CD4 + and CD8 + T E cells are mobilized to fight tumor cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HER2-enrich and basal-like carcinomas are characterized by highest CD8 tumor infiltrating lymphocytes and highest frequencies of memory T cells 25 , 26 . Researches in both human and mouse models have indicated that CD8 + T EM cells are enriched in the bone marrow of breast cancer patients/animals, but deficient in malignant effusions 27 - 29 . During the development of breast cancer, the human immune system is activated, and both CD4 + and CD8 + T E cells are mobilized to fight tumor cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In regard of the huge number of publications dealing with DCs in secondary organs or even in tissues, very few are focused on mature BM DCs. As in other tissues, DCs represent a small population of BM cells (1–2%) expressing high levels of CD103 (118, 119). They are mainly located in the perivascular region where they form clusters, interact with T cells and provide survival signals to B cells (119).…”
Section: Diversity In Osteoclast Originmentioning
confidence: 99%
“…This appeared sufficient to obtain peak anti-tumor DTH reactivity. This means three rounds of expansion and retraction of tumor-reactive T cells involving three waves of memory T cells changing between a status of activated effector memory (EMT) T cells in peripheral tissues and of resting central memory (CMT) T cells in the bone marrow [29]. …”
Section: Treatment Of Cancer Patients By Autologous Tumor Cell Vacmentioning
confidence: 99%